Presenting a Model of Obsessive-Compulsive Disorder Based on Family Functioning and Life Stressors with the Mediation of Perfectionism in Students - Shaham, Leila; Amirfakhra, Azita; Asadzadeh, Hasan (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: Obsessive-compulsive disorder (OCD) negatively impacts thoughts, beliefs, cognitions, and emotions. Therefore, the aim of this study was to present a model of OCD based on family functioning and life stressors with the mediation of perfectionism in students.Methods and Materials: This cross-sectional correlational study was conducted on students in Tehran during the 2020-2021 academic year. The sample size was 404 participants, selected through multistage cluster sampling. The research instruments included the Obsessive-Compulsive Inventory (Hodgson & Rachman, 1977), Family Assessment Device (Epstein et al., 1983), Life Events Scale (Pekel et al., 1971), and the Multidimensional Perfectionism Scale (Frost et al., 1990). Data analysis was performed using structural equation modeling with path analysis in SPSS and PLS software.Findings: The results showed that the model of OCD based on family functioning and life stressors with the mediation of perfectionism in students had a good fit. Additionally, family functioning and life stressors had a direct and significant effect on perfectionism and OCD, and perfectionism had a direct and significant effect on OCD (P < 0.05). Furthermore, family functioning and life stressors had an indirect and significant effect on OCD through the mediation of perfectionism (P < 0.05).Conclusion: The findings indicate the significant mediating role of perfectionism in the relationship between family functioning and life stressors with OCD. Therefore, to reduce OCD, interventions can focus on improving family functioning, reducing life stressors, and enhancing perfectionism.